Effect of Brewery Spent Grain Level and Fermentation Time on the Quality of Bread - Tadlo Yitayew; Demewez Moges; Neela Satheesh (International Journal of Food Science)
BSG (brewery spent grain) is the most frequent by-product from the beer industry, which is high in protein, fiber, and minerals. This research was carried out to improve the nutritional content of bread by adding BSG to wheat flour. In this study, five levels (0%, 5%, 10%, 15%, and 20%) of BSG blending ratio and three levels (1, 2, and 3 hrs) of fermentation time were considered. Standard procedures were used to determine the chemical composition of BSG, dough quality, physicochemical composition, and sensory quality of bread. The BSG is composed of 6.19% moisture, 4.01% ash, 8.80% crude fat, 16.80% crude fiber, 21.86% crude protein, 42.30% carbohydrate, 2.57 mg/g calcium, 3.16 mg/g magnesium, and 7.34 mg/g potassium. The dough water absorption (58.53-66.67 ml/100 g), development time (3.43-17.57 min), stability (6.53–12.40 min), and degree of softening (25.33-50.33 FU) were increased significantly (p<0.05) as BSG ratio increased in blending. As the BSG raised, the loaf weight (127.58-148.85 g) was increased and reduced the loaf volume (372.97–366.74 cm3). The proximate composition of the BSG blended bread was increased significantly from 33.19 to 45.29% moisture, 1.31 to 3.82% ash, 0.88 to 3.63% crude fat, 0.74 to 8.45% crude fiber, and 8.33 to 14.65% crude protein. The utilizable carbohydrate and energy values were decreased from 53.18 to 34.45% and 2.66 to 2.24 kcal, respectively. The calcium, magnesium, and potassium contents of the bread were increased from 76.44 to 150.93 mg/100 g, 87.12 to 176.81 mg/100 g, and 116.04 to 225.49 mg/100 g, respectively, as the BSG level was increased from 0 to 20%. However, the fermentation time had a significant effect (p<0.05) only on the moisture content, protein content, caloric value, and mineral content of bread. The sensory acceptance of bread was significantly affected (p<0.05) by BSG levels. Finally, by considering the sensory, other functional, and nutritional properties, we concluded that replacing the wheat flour with BSG up to 10% was accepted by the consumers.